Healthcare costs in relation to increased use of preoperative renal tumour biopsies - Agnes Lind; Bassam Mazin Hashim; Matilda Hagman; Susanna Holst; Andreas Karlsson Rosenblad; Börje Ljungberg; Per-Olof Lundgren; Sven Lundstam; Camilla Nystrand; Fanny Goude; Tobias Lauritsen (Scandinavian Journal of Urology)
Objective: To analyse the budget impact of adopting routine renal tumour biopsy (RTB) prior to decision on surgical treatment for clinical T1 renal tumours in Sweden.